2004
DOI: 10.1590/s1415-54192004000600011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do coeficiente de atrito de braquetes metálicos e estéticos com fios de aço inoxidável e beta-titânio

Abstract: Um fator importante que define a eficácia dos aparelhos ortodônticos fixos é o atrito existente entre as superfícies de fios e braquetes. Assim, este estudo teve como objetivo investigar o coeficiente de atrito estático entre fios de aço inoxidável e beta-titânio (TP Orthodontics) e braquetes de aço inoxidável (Dynalock® - Unitek), braquetes estéticos com slot de aço inoxidável (Clarity® - Unitek) e estéticos convencionais (Allure® - GAC). Para tanto, construiu-se um equipamento no Departamento de Engenharia M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, their levels of SF remained higher than those registered with metal brackets. 19 This difference may be due to the different ceramic and metal expansion coefficients, 4 or to the presence of a gap between the ceramic bracket body and the metal slot 20 what could be responsible for an inaccurate adaptation between these two major components, compromising its clinical performance.…”
Section: Variables That May Influence Friction During Otmmentioning
confidence: 99%
“…However, their levels of SF remained higher than those registered with metal brackets. 19 This difference may be due to the different ceramic and metal expansion coefficients, 4 or to the presence of a gap between the ceramic bracket body and the metal slot 20 what could be responsible for an inaccurate adaptation between these two major components, compromising its clinical performance.…”
Section: Variables That May Influence Friction During Otmmentioning
confidence: 99%
“…In addition, Downing et al 19 and Kusy, Whitley 20 observed that the wire material has little influence on the frictional force. In contrast, Braga et al 21 found that esthetic wires produce higher friction when compared to stainless-steel wires and pointed out that the differences observed might be related to the surface texture of the brackets. Moreover, the higher frictional resistance found for metallic wires can be explained by the difference in the friction levels between the different tested wires.…”
Section: Discussionmentioning
confidence: 91%
“…The brackets were bonded with epoxy resin to a metal support and the set was placed in a universal testing machine for traction of the stainless steel wire segment with a rectangular section of 0.019 x 0.025-in, at 0.5 mm/min at a total of 8.0 mm displacement in dry medium (Fig 3). According to information provided by manufacturers, the polycarbonate composite brackets are injected parts with a density of 1.4 g/cm 3 and typical hardness of 74 in the Shore scale; and conventional or unsintered metal brackets had a density of 7.4 to 7.9 g/cm 3 . The instruments for ligation were the Steiner or the Mathieu tying pliers, which were used, for each experimental situation, by the same operator using a 0.010-in-thick stainless steel wire (10 loops).…”
Section: Methodsmentioning
confidence: 99%
“…8 Frictional forces pose clinical challenges: they should be understood and controlled because their increase may be an advantage when used for anchorage, but harmful because of their effects in sliding mechanics. 12 The nature of friction in orthodontics depends on several factors and is determined by mechanical and biological factors: 1,3,9 Physical/mechanical factors…”
Section: Introductionmentioning
confidence: 99%